Calculation method for using amount of conductive agent for negative electrode of lithium ion battery and application of calculation method in production of lithium ion battery
By using the formula mCB negative = α*(s*h*μ/γ) in lithium-ion batteries, the problem that the content of conductive agent affects battery performance is solved, the slurry formula is optimized, and the battery performance and reliability are improved. It reduces the number of experiments and promotes the product research and development process.
Patent Information
- Application Number
- CN202411374271.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
In the manufacture of lithium-ion batteries, excessive or too little content of conductive agent will affect the performance of the battery, resulting in a decrease in electroporating or cycling performance, and it is difficult for the prior art to accurately calculate the amount of conductive agent to optimize the slurry formula.
Provide a method for calculating the amount of conductive agent used in the negative electrode of lithium-ion battery, and calculates the weight of conductive agent by the formula mCB negative = α*(s*h*μ/γ), where α is the negative electrode liquid retention conversion coefficient, s is the dressing area, h It is the thickness of the dressing, μ is the porosity, and γ is the oil absorption value of the conductive agent to ensure that the conductive agent content meets the liquid retention requirements without excessive amounts, and optimizes the slurry formula.
By calculating the conductive agent content in advance, optimizing the slurry formula, improving the performance and reliability of the battery, reducing the number of experiments, and accelerating the product development process, ensuring that the conductive agent can not only meet the liquid retention requirements without reducing the slurry performance.
Smart Images

Figure BDA0005068312240000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for calculating the amount of a negative electrode conductive agent used in a lithium ion battery and an application of the method in lithium ion battery production. Background Art
[0002] In the manufacture of lithium-ion batteries, conductive agents need to be added to improve the performance of the battery cells. Among the negative electrodes of lithium-ion batteries, most of the commercially used negative electrodes are graphite-based. These graphite-based negative electrodes themselves are conductive. Therefore, the purpose of adding conductive agents to the negative electrode is not only to improve the conductivity of the electrode, but more importantly, to adsorb and retain the electrolyte through its pore structure and capillary effect, improve the uniform distribution and utilization efficiency of the electrolyte, and thus improve the cycle performance and overall performance of the battery.
[0003] The content of conductive agent also has a significant impact on the performance of the battery. Too much conductive agent means less active ingredient and low capacity; too little conductive agent means poor conductivity and the battery is prone to polarization. Therefore, adding an appropriate amount of conductive agent is crucial.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a method for calculating the amount of negative electrode conductive agent used in a lithium ion battery to solve the above technical problems.
[0006] The second object of the present invention is to provide application of the above calculation method in lithium ion battery production.
[0007] In order to achieve the above objectives, the following technical solutions are adopted:
[0008] In a first aspect, the present invention provides a method for calculating the amount of negative electrode conductive agent used in a lithium ion battery, wherein the negative electrode sheet of the lithium ion battery comprises a current collector and a negative electrode slurry layer coated on the current collector;
[0009] The negative electrode slurry comprises a negative electrode active material, a negative electrode conductive agent and a binder;
[0010] In the negative electrode slurry, the calculation formula for the amount of negative electrode conductive agent is as follows:
[0011] m CB负 =α*(s*h*μ / γ);
[0012] Among them, m CB负 is the weight of the negative electrode conductive agent; α is the negative electrode liquid retention conversion coefficient; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the negative electrode conductive agent;
[0013] The α=0.08-0.3.
[0014] As a further technical solution, the negative electrode conductive agent includes: one or more of conductive carbon black and acetylene black.
[0015] As a further technical solution, the negative electrode active material includes: graphite;
[0016] As a further technical solution, the binder includes one or more of CMC and SBR.
[0017] As a further technical solution, the mass proportion of the binder in the negative electrode slurry layer is 1.5%-3.5%.
[0018] As a further technical solution, the current collector includes copper foil.
[0019] In a second aspect, the present invention provides application of the above calculation method in lithium ion battery production.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The method for calculating the amount of negative electrode conductive agent for lithium ion batteries provided by the present invention can optimize the formula of the slurry by calculating the content of the conductive agent in advance, ensuring that the content of the conductive agent can meet the requirements of liquid retention and will not be too much to cause a decrease in slurry performance, thereby improving the performance and reliability of the battery, and also reducing the number of experiments and accelerating the product development process. DETAILED DESCRIPTION
[0022] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0023] In a first aspect, the present invention provides a method for calculating the amount of negative electrode conductive agent used in a lithium ion battery, wherein the negative electrode sheet of the lithium ion battery comprises a current collector and a negative electrode slurry layer coated on the current collector;
[0024] The negative electrode slurry comprises a negative electrode active material, a negative electrode conductive agent and a binder;
[0025] In the negative electrode slurry, the calculation formula for the amount of negative electrode conductive agent is as follows:
[0026] m CB负 =α*(s*h*μ / γ);
[0027] Among them, m CB负 is the weight of the negative electrode conductive agent; α is the negative electrode liquid retention conversion coefficient; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the negative electrode conductive agent, which is preferably in the range of 250-350;
[0028] The α=0.08-0.3.
[0029] The principles of this solution are as follows:
[0030] Under ideal conditions, the surface of the negative electrode active material is uniformly coated with a layer of conductive agent (the ratio of the diameter of the negative electrode active material to the diameter of the conductive agent is, for example, in the range of 165-500). Assume that the dressing area of the negative electrode slurry is S; the dressing thickness of the negative electrode slurry is h; the porosity of the negative electrode slurry layer is μ; the oil absorption value of the negative electrode conductive agent is γ (mL / 100g); then the volume of the negative electrode is S*h, the pore volume of the negative electrode is S*h*μ, and the conductive agent content corresponding to the electrolyte that the negative electrode can absorb is s*h*μ / γ. Considering practical applications, the negative electrode liquid retention conversion coefficient α is designed according to actual experience. Therefore, the conductive agent dosage formula is mCB negative = α*(s*h*μ / γ).
[0031] Based on the fact that the negative electrode conductive agent mainly plays the function of absorbing electrolytic night to achieve liquid retention, the present invention provides a method for calculating the amount of negative electrode conductive agent used in lithium ion batteries. By calculating the content of the negative electrode conductive agent in advance, the formula of the slurry can be optimized to ensure that the content of the conductive agent can both meet the requirements of liquid retention and not be too much to cause a decrease in slurry performance, thereby improving the performance and reliability of the battery, while also reducing the number of experiments and accelerating the product development process.
[0032] In some optional embodiments, the negative electrode conductive agent includes but is not limited to one or more of conductive carbon black and acetylene black, or other negative electrode conductive agents known to those skilled in the art.
[0033] In some optional embodiments, the negative electrode active material includes: graphite.
[0034] In some optional embodiments, the binder is CMC+SBR, and the mass ratio of CMC to SBR is 1:1.
[0035] As a further technical solution, the mass proportion of the binder in the negative electrode slurry layer is 1.5%-3.5%.
[0036] In some optional embodiments, the current collector comprises copper foil.
[0037] In a second aspect, the present invention provides application of the above calculation method in lithium ion battery production.
[0038] The content of the negative electrode conductive agent calculated by the calculation method of the present invention can ensure that the content of the conductive agent can meet the requirements of liquid retention and will not be too much to cause a decrease in slurry performance, thereby improving the performance and reliability of the battery, while also reducing the number of experiments and accelerating the product development process.
[0039] The present invention is further described below by means of specific examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0040] Example 1
[0041] A method for calculating the amount of negative electrode conductive agent used in lithium-ion batteries. The calculation formula for the amount of negative electrode conductive agent used is as follows: m CB负 =α*(s*h*μ / γ);
[0042] Among them, m CB负 is the weight of the conductive agent; α is the negative electrode liquid retention conversion coefficient, which is 0.08; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the conductive agent.
[0043] Example 2
[0044] A method for calculating the amount of negative electrode conductive agent used in lithium-ion batteries. The calculation formula for the amount of negative electrode conductive agent used is as follows: m CB负 =α*(s*h*μ / γ);
[0045] Among them, m CB负 is the weight of the conductive agent; α is the negative electrode liquid retention conversion coefficient, which is 0.2; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the conductive agent.
[0046] Example 3
[0047] A method for calculating the amount of negative electrode conductive agent used in lithium-ion batteries. The calculation formula for the amount of negative electrode conductive agent used is as follows: m CB负 =α*(s*h*μ / γ);
[0048] Among them, m CB负 is the weight of the conductive agent; α is the negative electrode liquid retention conversion coefficient, which is 0.3; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the conductive agent.
[0049] Comparative Example 1
[0050] A method for calculating the amount of negative electrode conductive agent used in lithium-ion batteries. The calculation formula for the amount of negative electrode conductive agent used is as follows: m CB负 =α*(s*h*μ / γ);
[0051] Among them, m CB负 is the weight of the conductive agent; α is the negative electrode liquid retention conversion coefficient, which is 0.01; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the conductive agent.
[0052] Comparative Example 2
[0053] A method for calculating the amount of negative electrode conductive agent used in lithium-ion batteries. The calculation formula for the amount of negative electrode conductive agent used is as follows: m CB负 =α*(s*h*μ / γ);
[0054] Among them, m CB负 is the weight of the conductive agent; α is the negative electrode liquid retention conversion coefficient, which is 1; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the conductive agent.
[0055] Test Example 1
[0056] Graphite was used as the negative electrode active material, conductive carbon black was used as the conductive agent, CMC+SBR was used as the binder (wherein the mass ratio of CMC to SBR was 1:1), and a small amount of NMP was mixed and then coated on copper foil to prepare a negative electrode sheet. The amount of the conductive agent was calculated using the calculation method of Example 1-3 and Comparative Example 1-2:
[0057] s=10068cm 2 , h = 117.4 μm, μ = 38.91%, γ = 250 ml / 100 g; active material diameter = 10 μm; conductive agent diameter = 20 nm;
[0058] By calculation, m in Example 1 CB负 =
[0059] 0.08*10068*117.4 / 10000*38.91% / 250*100 / 1000=0.0014kg;
[0060] Example 2 m CB负 =0.2*10068*117.4 / 10000*38.91% / 250*100 / 1000=0.0036kg;
[0061] Example 3 m CB负 =0.3*10068*117.4 / 10000*38.91% / 250*100 / 1000=0.0055kg;
[0062] m of Comparative Example 1 CB负
[0063] =0.01*10068*117.4 / 10000*38.91% / 250*100 / 1000=0.0001kg;
[0064] m of Comparative Example 2 CB负 =1*10068*117.4 / 10000*38.91% / 250*100 / 1000=0.018kg;
[0065] Then, the conductive agent obtained by the above calculation was mixed with 0.15383 kg of negative electrode active material and 0.0066 kg of binder and coated on copper foil to obtain a negative electrode sheet.
[0066] Positive electrode sheet: The current collector is aluminum foil, and the slurry layer components are composed of positive electrode active material lithium iron phosphate, conductive agent graphite and binder PVDF, among which the positive electrode active material, conductive agent and binder account for 95.2%:2.5%:2.3%.
[0067] Diaphragm: PE diaphragm.
[0068] Electrolyte: The electrolyte is lithium hexafluorophosphate (1 mol / L), and the solvent is ethylene carbonate and dimethyl carbonate, the ratio of the two is 1:1, and the electrolyte contains 2% by weight of vinylene carbonate.
[0069] The negative electrode sheets prepared in Examples 1-3 and Comparative Examples 1-2 were respectively combined with the positive electrode sheets, separators and electrolytes to prepare lithium-ion batteries, and then the performance of the batteries was tested. The results are as follows:
[0070]
[0071]
[0072] Note: First efficiency: Coulombic efficiency of the battery in the first charge and discharge cycle; Cycle: Discharge capacity retention rate after 1000 charge and discharge cycles at 0.5C at 25 degrees; Rate: Capacity retention rate when the initial capacity is charged at 0.2C and discharged at 0.2C at 25 degrees, and charged at 0.2C and discharged at 1C; Storage: Capacity retention rate after 30D (30 days) of storage at 100% SOC at 25 degrees.
[0073] It can be seen from the experimental results that if the content of the conductive agent is too little, the cycle performance and rate performance of the battery will be reduced, and if the content of the conductive agent is too much, the first coulombic efficiency of the battery will be reduced.
[0074] Test Example 2
[0075] Graphite is used as the negative electrode active material, acetylene black is used as the conductive agent, SBR is used as the binder, and a small amount of NMP is mixed and coated on copper foil to prepare a negative electrode sheet. The amount of the conductive agent is calculated using the calculation method of Example 1-3 and Comparative Example 1-2:
[0076] s=10068cm 2 , h=112μm, μ=38.91%, γ=350ml / 100g; active material diameter=10μm; conductive agent diameter=25nm.
[0077] By calculation, m in Example 1 CB负 =
[0078] 0.08*10068*112 / 10000*38.91% / 350*100 / 1000=0.0010kg;
[0079] Example 2 m CB负 =0.2*10068*112 / 10000*38.91% / 350*100 / 1000=0.0025kg;
[0080] Example 3 m CB负 =0.3*10068*112 / 10000*38.91% / 350*100 / 1000=0.0037kg;
[0081] m of Comparative Example 1 CB负 =0.01*10068*112 / 10000*38.91% / 350*100 / 1000=0.0001kg;
[0082] m of Comparative Example 2 CB负 =1*10068*117.4 / 10000*38.91% / 350*100 / 1000=0.0125kg;
[0083] Then, the conductive agent obtained by the above calculation was mixed with 0.15383 kg of negative electrode active material and 0.0066 kg of binder and coated on copper foil to obtain a negative electrode sheet.
[0084] Positive electrode sheet: The current collector is aluminum foil, and the slurry layer components are composed of positive electrode active material lithium iron phosphate, conductive agent graphite and binder PVDF, among which the positive electrode active material, conductive agent and binder account for 95.2%:2.5%:2.3%.
[0085] Diaphragm: PE diaphragm.
[0086] Electrolyte: The electrolyte is lithium hexafluorophosphate (1 mol / L), and the solvent is ethylene carbonate and dimethyl carbonate, the ratio of the two is 1:1, and the electrolyte contains 2% by weight of vinylene carbonate.
[0087] The negative electrode sheets prepared in Examples 1-3 and Comparative Examples 1-2 were respectively combined with the positive electrode sheets, separators and electrolytes to prepare lithium-ion batteries, and then the performance of the batteries was tested. The results are as follows:
[0088] Test Example 1 First effect cycle Ratio (0.2C / 1C) Storage (30D) Example 1 89.55% 1000cls@85.78% 96.65% 97.98% Example 2 90.56% 1000cls@86.76% 97.66% 98.50% Example 3 90.72% 1000cls@86.89% 97.87% 98.77% Comparative Example 1 90.19% 1000cls@73.07% 90.46% 92.98% Comparative Example 2 88.93% 1000cls@86.03% 97.11% 97.65%
[0089] Test Example 3
[0090] Graphite is used as the negative electrode active material, conductive carbon black is used as the conductive agent, SBR is used as the binder, and a small amount of NMP is mixed and coated on copper foil to prepare the negative electrode sheet. The amount of the conductive agent is calculated using the calculation method of Example 1-3 and Comparative Example 1-2:
[0091] s=10068cm 2 , h = 117 μm, μ = 38.91%, γ = 300 ml / 100 g; active material diameter = 10 μm; conductive agent diameter = 22 nm.
[0092] By calculation, m in Example 1 CB负 =
[0093] 0.08*10068*112 / 10000*38.91% / 300*100 / 1000=0.0012kg;
[0094] Example 2 m CB负 =0.2*10068*112 / 10000*38.91% / 300*100 / 1000=0.003kg;
[0095] Example 3 m CB负 =0.3*10068*112 / 10000*38.91% / 300*100 / 1000=0.0045kg
[0096] m of Comparative Example 1 CB负 =0.01*10068*112 / 10000*38.91% / 300*100 / 1000=0.0001kg;
[0097] m of Comparative Example 2 CB负 =1*10068*117.4 / 10000*38.91% / 300*100 / 1000=0.015kg;
[0098] Then, the conductive agent obtained by the above calculation was mixed with 0.15383 kg of negative electrode active material and 0.0066 kg of binder and coated on copper foil to obtain a negative electrode sheet.
[0099] Positive electrode sheet: The current collector is aluminum foil, and the slurry layer components are composed of positive electrode active material lithium iron phosphate, conductive agent graphite and binder PVDF, among which the positive electrode active material, conductive agent and binder account for 95.2%:2.5%:2.3%.
[0100] Diaphragm: PE diaphragm.
[0101] Electrolyte: The electrolyte is lithium hexafluorophosphate (1 mol / L), and the solvent is ethylene carbonate and dimethyl carbonate, the ratio of the two is 1:1, and the electrolyte contains 2% by weight of vinylene carbonate.
[0102] The negative electrode sheets prepared in Examples 1-3 and Comparative Examples 1-2 were respectively combined with the positive electrode sheets, separators and electrolytes to prepare lithium-ion batteries, and then the performance of the batteries was tested. The results are as follows:
[0103] Test Example 1 First effect cycle Ratio (0.2C / 1C) Storage (30D) Example 1 89.04% 1000cls@85.02% 96.40% 97.66% Example 2 90.37% 1000cls@86.39% 97.26% 98.96% Example 3 90.80% 1000cls@86.81% 97.57% 98.99% Comparative Example 1 90.38% 1000cls@71.4% 90.69% 92.15% Comparative Example 2 88.00% 1000cls@86.41% 97.80% 97.26%
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for calculating the amount of negative electrode conductive agent for lithium ion batteries, characterized in that: The negative electrode sheet of the lithium ion battery comprises a current collector and a negative electrode slurry layer coated on the current collector; The negative electrode slurry comprises a negative electrode active material, a negative electrode conductive agent and a binder; In the negative electrode slurry, the calculation formula for the amount of negative electrode conductive agent is as follows: m CB负 =α*(s*h*μ / γ); Among them, m CB负 is the weight of the negative electrode conductive agent; α is the negative electrode liquid retention conversion coefficient; s is the dressing area of the negative electrode slurry; h is the dressing thickness of the negative electrode slurry; μ is the porosity of the negative electrode slurry layer; γ is the oil absorption value of the negative electrode conductive agent; The α=0.08-0.
3.
2. The calculation method according to claim 1, characterized in that: The negative electrode conductive agent includes: one or more of conductive carbon black and acetylene black.
3. The calculation method according to claim 1, characterized in that: The negative electrode active material includes graphite.
4. The calculation method according to claim 1, characterized in that: The binder includes one or more of CMC and SBR.
5. The calculation method according to claim 1, characterized in that: The mass proportion of the binder in the negative electrode slurry layer is 1.5%-3.5%.
6. The calculation method according to claim 1, characterized in that: The current collector includes copper foil.
7. Application of the calculation method according to any one of claims 1 to 6 in the production of lithium-ion batteries.